Evaluasi Standar Pelayanan Minimal Instalasi Farmasi RSUD Waluyo Jati Kraksaan Sebelum dan Sesudah Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan - Amelia Kusuma Krisnadewi; Prihwanto Budi Subagio; Wiratmo Wiratmo (Pustaka Kesehatan, 2014)
Health care is a right of every person to be realized with the efforts to increase community health status. Social Security Agency of Health (Health BPJS) is an organization statutory to set up the health insurance program that worked on January 1, 2014. Hospital as one of the individual health care which part of the health resources that are indispensable in support of health efforts. One of the health care provided by the hospital pharmaceutical care. The first stage is carried out using a questionnaire and the data collection sheet instruments observation of indicators pharmaceutical care. Stages of data processing carried out by methods that include normality test, T test to 2 free samples, Mann Whitney test. The last stage is draw conclusions achievement Waluyo Jati Hospital Pharmacy SPM on Hospital Pharmacy SPM which has been determined by the Minister of Health. The results of the study in Pharmacy Waluyo Jati Kraksaan Hospital shows that Pharmacy SPM achievement of Waluyo Jati Kraksaan Hospital is in conformity set by the Minister of Health of the Republic of Indonesia.